Specific concentration evaluation of 16% carbamide peroxide compounded at dispensing pharmacies Avaliação da concentração específica do peróxido de carbamida a 16% produzido em farmácias de manipulação - Juliana Maria Habith Martin; Vladja Torno; Marcos Vinícius da Silveira Vaz; Sérgio Vieira; Edvaldo Antonio Ribeiro Rosa; Rui Fernando Mazur (Sociedade Brasileira de Pesquisa Odontológica, 2007)
The aim of this work was to evaluate the concentration of carbamide peroxide compounded at different dispensing pharmacies. Immediate concentration analysis was made of bleaching gels dispensed by specialized pharmacies, and of a commercially available gel (control group) (n = 20). The carbamide peroxide concentration was determined by titration and the results were analyzed statistically by the Kruskal-Wallis test. The commercial bleaching agent (control group) and one of the gels from the pharmacies presented the best mean concentration values, close to 16%. In conclusion, the concentration of the manipulated and industrialized carbamide peroxide gels presented concentration values differing from 16%. O objetivo deste trabalho foi avaliar a concentração do peróxido de carbamida manipulado em diferentes farmácias de manipulação. Foram utilizados géis clareadores manipulados em farmácias especializadas e um industrializado (grupo controle) (n = 20) com análise de concentração imediata. A concentração do peróxido de carbamida foi obtida por titulometria e os resultados foram submetidos a análise estatística pelo teste de Kruskal-Wallis. Como resultado, o agente clareador (controle) e um dos produtos manipulados em farmácia apresentaram as melhores médias de concentração, próximas a 16%. Pode-se concluir que a concentração do peróxido de carbamida manipulado e dos industrializados apresentaram valores de concentração diferentes de 16%.